The Return of Traditional Indigenous Midwifery Practices in Quebec - Basile, Suzy; Kermoal, Nathalie; Comat, Ioana; Asselin, Hugo (The International Indigenous Policy Journal, 2026)
Indigenous mothers face unique challenges and violence when they seek assistance from the healthcare system for themselves and their unborn children. From the mid-20th century on, when Canada’s Indigenous communities were sedentarized, women were compelled to give birth in hospitals. By taking control of Indigenous women’s bodies, the hospital-based healthcare system altered the fundamental structure of Indigenous societies. Even when efforts were made to expand accessibility by creating community health facilities, Indigenous women were still forced to give birth in hospitals. By centering on Innu and Atikamekw women’s voices, we examine how Quebec’s medical colonialism has affected Indigenous women giving birth in medical facilities. We demonstrate how the healthcare system disrupts Indigenous practices and knowledge regarding pregnancy, childbirth and postnatal recovery, thus altering an entire communal support system. We also examine the growing movement among Quebec’s Indigenous communities to reclaim control over childbirth as a means of opposing medical colonialism, notably through the return of traditional midwifery practices.